Bacterial antigens in synovial biopsy specimens in yersinia triggered reactive arthritis. Issue 2 (February 1991) - Merilahti-Palo, R; Söderström, K O; Lahesmaa-Rantala, R; Granfors, K; Toivanen, A
Abstract : Non-viable structures of Yersinia enterocolitica O:3 were shown at the site of inflammation within mononuclear cells in the synovial membrane of eight out of 10 patients with yersinia triggered reactive arthritis. An avidin-biotin-peroxidase complex method, with a rabbit antiserum specific for Y enterocolitica O:3, was used to visualise yersinia structures. All 13 control samples were negative except for one with non-specific mast cell staining. The findings emphasise the significance of foreign material in the initiation of synovitis in reactive arthritis.